Peningkatan pengetahuan pengelolaan sampah organik rumah tangga dengan menggunakan maggot BSF sabagai pakan ternak - Gustina, Mely; Mulyati, Sri; Adeko, Riang; Ali, Haidina (JOURNAL OF Public Health Concerns, 2024)
Background: Waste is the remains of human daily activities and/or from natural processes in solid form. However, according to the Health Organization (WHO), waste is something that is not used, not used, not liked or something that is thrown away that comes from human activities and does not happen by itself . Piles of organic waste that are not managed properly can cause various environmental and health problems. As an innovative solution, this study examines the potential for cultivating maggots (Black Soldier Fly larvae) as an alternative to managing organic waste. Purpose: To provide knowledge and skills in maggot cultivation in the utilization of household organic waste as animal feed. Method: A total of 15 people participated in this activity. Through the presentation of materials, training and demonstrations in providing an understanding of the maggot cultivation process, from making cages to harvesting. Applying an active interaction method of asking questions about the material presented during the training activities. Results: Based on direct practice simulations in making BSF maggots as animal feed, packaging BSF maggots as animal feed that is ready to sell for marketing. The participants actively asked questions and discussed each sequence of its manufacture. The education and training provided by the resource person together with the service team could be accepted and applied by the participants, where participants stated that they would make and implement the utilization of household organic waste by using SBF maggots as animal feed both at home and in their residential environment in managing waste piles. The level of knowledge of participants regarding the utilization of household organic waste by using BSF maggots as animal feed increased from 15 people with poor knowledge to 12 people with good knowledge and 3 people with sufficient knowledge. Conclusion: Community service activities with education, training, and simulations on the utilization of household organic waste using BSF maggots as animal feed can increase community knowledge and skills in managing organic waste into independent business opportunities. Keywords: Black Soldier Fly; Creative entrepreneurship; Maggot cultivation; Organic waste management Pendahuluan: Sampah adalah sisa kegiatan sehari-hari manusia dan/atau dari proses alam yang berbentuk padat. Namun menurut Health Organization (WHO) sampah adalah sesuatu yang tidak digunakan, tidak dipakai, tidak disenangi atau sesuatu yang dibuang yang berasal dari kegiatan manusia dan tidak terjadi dengan sendirinya. Tumpukan sampah organik yang tidak terkelola dengan baik dapat menimbulkan berbagai masalah lingkungan dan kesehatan. Sebagai solusi inovatif, penelitian ini mengkaji potensi budidaya maggot (larva lalat Black Soldier Fly) sebagai alternatif pengelolaan sampah organik. Tujuan: Untuk memberikan pengetahuan dan keterampilan budidaya maggot dalam pemanfaatan sampah organik rumah tangga sebagai pakan ternak.   Metode: Sebanyak 15 orang menjadi peserta dalam kegiatan ini. Melalui pemaparan materi, pelatihan dan demonstrasi dalam memberikan pemahaman mengenai proses budidaya maggot, mulai dari pembuatan kandang hingga pemanenan. Menerapkan mentode interaksi aktif bertanya mengenai materi yang disampaikan ketika kegiatan pelatihan berlangsung. Hasil: Berdasarkan simulasi praktik langsung dalam membuat maggot BSF sebagai pakan ternak, pengemasan maggot BSF sebagai pakan ternak yang siap jual untuk dipasarkan. Para peserta turut aktif bertanya dan berdiskusi di setiap runtutan pembuatannya. Edukasi dan pelatihan yang diberikan oleh narasumber bersama tim pengabdi bisa diterima dan bisa diaplikasikan oleh para peserta, dimana peserta menyatakan akan membuat dan menerapkan pemanfaatan sampah organik rumah tangga dengan menggunakan maggot SBF sebagai pakan ternak baik di rumah maupun di lingkungan tempat tinggalnya dalam mengelola timbunan sampah. Tingkat pengetahuan peserta mengenai pemanfaatan sampah organik rumah tangga dengan menggunakan maggot BSF sebagai pakan ternak meningkat dari sebanyak 15 orang dengan tingkat pengetahuan kurang menjadi sebanyak 12 orang dengan tingkat pengetahuan baik dan sebanyak 3 orang dengan tingkat pengetahuan cukup. Simpulan: Kegiatan pengabdian masyarakat dengan edukasi, pelatihan, dan simulasi tentang pemanfaatan sampah organik rumah tangga dengan menggunakan maggot BSF sebagai pakan ternak dapat meningkatkan pengetahuan dan keterampilan masyarakat dalam mengelola limbah sampah organik menjadi peluang usaha mandiri.